2014
DOI: 10.3109/13561820.2014.942837
|View full text |Cite
|
Sign up to set email alerts
|

French translation and validation of the Readiness for Interprofessional Learning Scale (RIPLS) in a Canadian undergraduate healthcare student context

Abstract: The Canadian Interprofessional Health Collaborative recommends that future professionals be prepared for collaborative practice. To do so, it is necessary for them to learn about the principles of interprofessional collaboration. Therefore, to ascertain if students are predisposed, their attitude toward interprofessional learning must be assessed. In the French Canadian context such a measuring tool has not been published yet. The purpose of this study is to translate in French an adapted version of the RIPLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…The index values obtained in the present study were higher than those obtained from other RIPLS adaptation studies; as a result, the structure of the tested Turkish version of the scale is thought to be consistent. In the present study, after CFA, similar values were obtained with the structure suggested and confirmed by Parsell and Bligh 21 and with those tested and confirmed by Lauffs et al 23 and Mahler et al 26 With the exception of Cloutier et al, 25 the team and collaboration sub-scale in all studies was consistent with the results of Parsell and Bligh. 21 The lowest degree of reliability was obtained in the roles and responsibilities sub-scale in the present study; similarly, Parsell's study also yielded low levels of reliability in the same sub-scale.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The index values obtained in the present study were higher than those obtained from other RIPLS adaptation studies; as a result, the structure of the tested Turkish version of the scale is thought to be consistent. In the present study, after CFA, similar values were obtained with the structure suggested and confirmed by Parsell and Bligh 21 and with those tested and confirmed by Lauffs et al 23 and Mahler et al 26 With the exception of Cloutier et al, 25 the team and collaboration sub-scale in all studies was consistent with the results of Parsell and Bligh. 21 The lowest degree of reliability was obtained in the roles and responsibilities sub-scale in the present study; similarly, Parsell's study also yielded low levels of reliability in the same sub-scale.…”
Section: Discussionsupporting
confidence: 81%
“…Different studies show inconsistent results for the professional identity sub-scale. [21][22][23]26 The most outstanding results among the adaptation studies were obtained by Cloutier et al 25 The 18 th and 19 th items in that study were excluded, and the remaining items were associated with different, re-named factors. The titles of the sub-scales and their associations with the factors are different in the Japanese 24 and the French 25 adaptations of the original scale; when those adaptation studies were investigated, it was noted that an approach that considered cultural differences and subject fields was necessary to obtain similar results to the original scale.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations